Hysterosalpingography in Infertility - Khan, Masuda Islam; Jesmin, Suha; Jerin, Jesmin; Shermin, Shahana; Chowdhury, TA (Delta Medical College Journal, 2014)
Background: Infertility is a common medical problem. It can be due to problems in either partner, or both. Ovulatory dysfunction, tubal and peritoneal factors comprise the majority of female factor for infertility. Hysterosalpingography (HSG) plays an important role in the evaluation of abnormalities related to the uterus and fallopian tubes. Objective: The aim of this study was to evaluate the hysterosalpingographic findings of women with infertility in our setting. Materials and method: This cross sectional study was carried out in the infertility centre at BIRDEM, Dhaka, Bangladesh during the period of September 2002 to February 2003. Out of 100 infertile patients 50 infertile women of reproductive age (21-40 years) indicated for HSG were enrolled in this study. Results: Sixty percent patients had secondary infertility. Majority of the subjects of both primary and secondary infertility (55% and 60%) were in 26-30 years age group. On HSG any sort of uterine pathology was found in 10% cases and unilateral and bilateral tubal block were present in 24% and 20% cases respectively. Conclusion: Hysterosalpingography, a safe, less invasive procedure, has an important role in diagnosing uterine and tubal factors of infertility. DOI: http://dx.doi.org/10.3329/dmcj.v2i1.17790 Delta Med Col J. Jan 2014; 2(1): 9-12